Interactions Between the Fourth Industrial Revolution and Human Resource Management Meeting the Needs of Enterprises - Thao, Nguyen Thi Thu (Universitas Komputer Indonesia, 2024)
Managing the training of a skilled workforce capable of meeting job requirements in enterprises is crucial and urgent in the context of the emerging Fourth Industrial Revolution. This paper discusses the current state of the Fourth Industrial Revolution, provides examples from Vietnam, and suggests effective solutions for managing human resources in the current industrial revolution.